Kaitan Waktu Inisiasi MP-ASI dengan Konstipasi Fungsional pada Bayi Usia 6–12 Bulan: Literatur Review - Rizky Andriani Bakara; Emelia Apriani Tampubolon (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Early complementary feeding is associated with digestive disorders in infants, including constipation. This literature review aims to explore the relationship between the timing of complementary food (MP-ASI) introduction and the incidence of constipation in infants aged 6–12 months. Using a qualitative descriptive method, the review includes 9 research articles published between 2013 and 2023 from databases such as Google Scholar, PubMed, and ScienceDirect. The findings show that early MP-ASI (before 6 months of age) significantly increases the risk of constipation due to the immaturity of the infant's gastrointestinal system and low dietary fiber intake. Most studies highlight the physiological limitations of the infant's digestive system under six months and the importance of appropriate food timing and content. The implication of this review supports WHO and national health guidelines recommending complementary feeding initiation at 6 months of age. It also emphasizes the need for health education at the community level to prevent functional constipation in early life through correct feeding practices.